The Effect of Micro-architectural Structure of Cabbage Substratum and or Background Bacterial Flora on the Growth of Listeria Monocytogenes - Ongeng, Duncan; Ryckeboer, Jaak; Vermeulen, An; Devlieghere, Frank (International journal of food microbiology, 2007)
The effect of micro-architectural structure of cabbage (Brassica oleracea var. capitata L.) substratum and or background bacterial flora on the growth of Listeria monocytogenes as a function of incubation temperature was investigated. A cocktail mixture of Pseudomonas fluorescens, Pantoea agglomerans and Lactobacillus plantarum was constituted to a population density of approximately 5 log CFU/ml in order to pseudo-simulate background bacterial flora of fresh-cut cabbage. This mixture was co-inoculated with L. monocytogenes (approximately 3 log CFU/ml) on fresh-cut cabbage or in autoclaved cabbage juice followed by incubation at different temperatures (4–30 °C). Data on growth of L. monocytogenes were fitted to the primary growth model of Baranyi in order to generate the growth kinetic parameters of the pathogen. During storage, microbial ecology was dominated by P. fluorescens and L. plantarum at refrigeration and abuse temperature, respectively. At all temperatures investigated, lag duration (λ, h), maximum specific growth rate (μmax, h− 1) and maximum population density (MPD, log CFU/ml) of L. monocytogenes were only affected by medium micro-architectural structure, except at 4 °C where it had no effect on the μmax of the pathogen. Comparison of observed values of μmax with those obtained from the Pathogen Modelling Program (PMP), showed that PMP overestimated the growth rate of L. monocytogenes on fresh-cut cabbage and in cabbage juice, respectively. Temperature dependency of μmax of L. monocytogenes, according to the models of Ratkowsky and Arrhenius, showed linearity for temperature range of 4–15 °C, discontinuities and linearity again for temperature range of 20–30 °C. The results of this experiment have shown that the constituted background bacterial flora had no effect on the growth of L. monocytogenes and that micro-architectural structure of the vegetable was the primary factor that limited the applicability of PMP model for predicting the growth of L. monocytogenes on fresh-cut cabbage. A major limitation of this study however is that nutrient profile of the autoclaved cabbage juice may be different from that of the raw juice thus compromising realistic comparison of the behaviour of L. monocytogenes as affected by micro-architectural structure.
Keywords: Micro-architectural structure; Cabbage substratum; Background bacterial flora; Listeria monocytogenes